Transcriptional response of OmpC and OmpF in Escherichia coli against differential gradient of carbapenem stress - Chetri, Shiela (BMC Res Notes, 2019)
OBJECTIVE: This study was designed to investigate the transcriptional response of OmpF and OmpC along with an antisense RNA, MicF under concentration gradient carbapenem exposure. RESULT: An elevation in the expression of OmpF gene under concentration gradient imipenem stress from a particular concentration was observed. For OmpC gene a significant decrease in the expression was noticed under concentration gradient imipenem and meropenem stress. The study showed reduction in the expression of OmpC gene against imipenem and meropenem possibly preventing the entry of carbapenem antibiotic inside the cell indicating a possible role in carbapenem resistance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-019-4177-4) contains supplementary material, which is available to authorized users.